New objectives of the French high-speed rail system within the framework of a highly centralized network: A substitute for the domestic air transport market? - Pierre Zembri (European Regional Science Association (ERSA), 2010)
The high speed rail network represents now a large part of the rail services, 4 sub-networks being concerned from/to Paris. The interoperability between high-speed trunk lines and the rest of the electrified network permits a large coverage of the French territory : the TGV services network is broader than the real high speed one. From the beginning of high-speed services in France, the main target of the TGV system has been business traffic using the domestic air transport network. The SNCF can be considered as an active player in the Air transport competition, offering low travel times, competitive prices and high capacities. The frequencies can be high between the largest towns : 16 round-trip services between Paris and Marseilles, 21 between Paris and Bordeaux, etc. The development of the TGV network creates new opportunities of competition with Air France and other carriers. That is one of the reasons of the relative weakness of competition within the domestic Air Transport sector. Air France is now planning a progressive downsizing of its domestic services on the lines where the market share of the TGV is growing. We have compared the level of service of the two carriers, according to the TGV average travel time (quite different from the real distance). Our main hypothesis is that Air France adapts its service level and its routes to the supposed state of competition. When most of the flights are oriented towards Orly airport (pure domestic market), the competition is at its advantage. When most of them are oriented to the CDG hub, the competition is over for Air France. The 'price war' has not the same intensity : air fares are higher when HST is not competitive or when the air lines are mostly used for feedering the main hub. The 'area of intense competition' is now between 150 and 300 minutes of HST average travel time, that is more than previously estimated. Most of the domestic and short-haul international routes from Paris, but also from other main towns like Marseilles or Lyon will be shortly concerned...
Keywords: 330; High-speed rail; air transport; domestic market; competition; network